Collaboration Between Content Experts and Assessment Specialists: Using a Validity Argument Framework to Develop a College Mathematics Assessment - Brijmohan, Amanda; Khan, Gulam A.; Orpwood, Graham; Sandford Brown, Emily; Childs, Ruth A. (Canadian Journal of Education/Revue canadienne de l'éducation, 2018)
Developing a new assessment requires the expertise of both content experts and assessment specialists. Using the example of an assessment developed for Ontario’s Colleges Mathematics Assessment Program (CMAP), this article (1) describes the decisions that must be made in developing a new assessment, (2) explores the complementary contributions of content experts and assessment specialists, and (3) illustrates how the use of a validity argument framework can support collaboration in assessment development. The authors conclude that the validity argument framework facilitated effective collaboration between content experts and assessment specialists, and suggest that this approach may help other collaborators pursue transparent and effective assessment development.